RAGAM KEGIATAN DAN PERMASALAHAN KEMITRAAN DUKUN BAYI DAN BIDAN DALAM PEMELIHARAAN KESEHATAN IBU DAN ANAK - Irfan Nafis Sjamsuddin; Tri Krianto (Sekolah Tinggi Ilmu Kesehatan Dharma husada, 2023)
The partnership between traditional birth attendants and midwives takes place in Indonesia without eliminating the existence of traditional birth attendants as a cultural heritage. The purpose of the study was to find out the various activities and problems in implementing the partnership in maintaining maternal and child health. Design research literature review, search for online articles at the Garuda Portal and Research Gate. The article review is followed by a synthesis using the article summary matrix. The results show the role of traditional birth attendants is the identification of new pregnant women, motivation for antenatal care and delivery by trained health workers, assisting midwives in childbirth, motivation if necessary referrals, education on healthy behavior during pregnancy and postpartum, postpartum maternal care, baby care, events culture according to local customs, and communication related to maternal and child health care. The role of the midwife is to conduct examinations of pregnant women, assist with childbirth, home visits for postpartum and newborn care, counseling on pregnancy-childbirth- postpartum and infant care, recording and referring cases if necessary. The problems are that not all traditional birth attendants have partnered for reasons of trust and economy, support from community leaders has not been optimal, partnership legislation has not been written, communication is hampered by language differences. Counseling to the community about the position of traditional birth attendants and midwives in maintaining maternal and child health, and guidance to all traditional birth attendants based-on the existing guidelines.